Kaplow, Louis. Rethinking Merger Analysis - Shapiro, Carl (Journal of Economic Literature, 2025)
Charles Shapiro of University of California, Berkeley reviews “Rethinking Merger Analysis” by Louis Kaplow. The Econlit abstract of this book begins: “Explores major questions relevant to the analysis of horizontal mergers, assessing the appropriate way to set research agendas, formulate policy, and determine how best to analyze proposed mergers.”